2018
DOI: 10.1128/jcm.00415-18
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a Potential Algorithm for Clostridium difficile Testing at a Tertiary Care Hospital: Does Toxin Enzyme Immunoassay Testing Help?

Abstract: is a major contributor to morbidity and mortality in the United States. Methods for identifying the organism in stool include molecular platforms, enzyme immunoassays (EIAs) for toxin, and culture. Controversy persists over whether molecular tests are too sensitive at identifying , and there are questions about how additional laboratory information could inform clinical management and reduce over treatment. The aim of this study was to assess whether clinical factors are related to the toxin status of patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 21 publications
1
5
0
2
Order By: Relevance
“…Additionally, this further supports the recommendation for PCR testing alone when pre-test probability is improved with stool submission criteria. [4] Similar to previous studies [11,[13][14], we observed no increase in adverse events when discordant cases were not treated. While this has been previously taken as support that discordant cases are most likely representative of colonization as opposed to true infection, the actual signi cance of these cases is unclear.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Additionally, this further supports the recommendation for PCR testing alone when pre-test probability is improved with stool submission criteria. [4] Similar to previous studies [11,[13][14], we observed no increase in adverse events when discordant cases were not treated. While this has been previously taken as support that discordant cases are most likely representative of colonization as opposed to true infection, the actual signi cance of these cases is unclear.…”
supporting
confidence: 89%
“…Indeed, several studies found no difference in clinical outcomes between discordant and concordant patients, irrespective of treatment. [11,[13][14] Accurate distinction between colonization and CDI is desirable because it results in cost savings, appropriate antimicrobial stewardship, accurate diagnosis, and decreases risks for vancomycin resistant Enterococcus colonization. [12] Our institution relied on a PCR-only testing strategy at the time of the 2018 guideline publication.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1‐2 ] It is attributed commonly to well‐aligned constituent enzymes in multienzyme cascade systems to ensure a series of catalytic reactions concurrently happening and not interfering with each other. [ 3 ] Drawing inspiration from nature, many research groups have been committed to constructing controllable spatial organization for specified enzyme pairs in the engineering applications of industrial manufacturing, [ 4‐5 ] biomedicine, [ 2,6‐7 ] materials, [ 8 ] and biosensors. [ 9‐10 ] These artificial systems include nanoparticles, [ 11 ] crystalline materials, [ 12 ] biomolecular cages, [ 13‐14 ] sol‐gel materials, [ 15‐16 ] LBL assembly materials, [ 17 ] metal‐organic frameworks, [ 14 ] polymersomes, [ 14,18 ] and so on.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Por otra parte, la detección de cepas con capacidad toxigénica mediante PCR o cultivo no implica necesariamente que haya toxina libre, pudiendo corresponder a casos de colonización, mientras que la citotoxicidad puede deberse a causas distintas al C. difficile . En el estudio de Theiss et al [ 12 ], en la mitad de los pacientes con PCR positiva no se pudo detectar toxina mediante una técnica de enzimoinmunoensayo (EIA), un porcentaje similar al de nuestro estudio. En otro estudio similar, Crobach et al sólo detectaron toxina en menos del 40% de las muestras positivas mediante PCR [ 13 ].…”
Section: Discussionunclassified
“…En nuestro estudio la gran mayoría de las muestras procesadas han sido diarreicas, lo que podría concordar con una clínica compatible con infección, sin embargo, la diarrea podría deberse a otras causas distintas a la acción del C. difficile [ 16 ]. Theiss et al no han observado diferencias en los síntomas ni en las características clínicas de los pacientes en función de si se detectan toxinas o no en las muestras con PCR positiva [ 12 ], lo que complica la identificación de los pacientes realmente infectados. La presencia de síntomas clínicos (fundamentalmente la diarrea) sin otra causa que los justifique puede ayudar a establecer un diagnóstico más fiable de la infección.…”
Section: Discussionunclassified